Pengaruh Pengetahuan, Promosi Dan Lokasi Terhadap Minat Menabung Pada Bank Syariah di Kelurahan Pandan Jaya Kabupaten Tanjung Jabung Timur - Lingga Kumala; Nazori Nazori; Efni Anita (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In general, many people choose to save and borrow money from financial institutions other than sharia banks, such as conventional banks and general cooperatives. In fact, conventional banks are known to adhere to an interest system which according to scholars is prohibited because interest is considered usury. Factors that can influence interest in saving at Islamic banks are knowledge, promotions and location. A person's knowledge about Islamic banks will influence customer interest, each bank tries to promote all the products and services it has, and the location of Islamic banks has easy assets. The aim of this research is to determine the influence of knowledge, promotion and location on the interest of the people of Pandan Jaya subdistrict, Tanjung Jabung Timur district to save in sharia banks. The type of research used in this research is quantitative descriptive research. The sample was selected using Accidental Sampling and the Slovin formula to obtain 98 respondents. The data analysis used is Multiple Linear Regression Analysis. The results of the research concluded that partially the variables knowledge, promotion and location had an influence on interest in saving at Sharia Banks in Pandan Jaya Village, East Tanjung Jabung Regency. Simultaneously, the variables of knowledge, promotion and location influence interest in saving at Sharia Banks in Pandan Jaya Village, East Tanjung Jabung Regency. Based on the coefficient of determination, it indicates that knowledge, promotion and location can influence interest in saving at Sharia Banks by 77.4%. It is hoped that people, especially Muslims, can save in sharia banks considering that sharia banks have used sharia principles in accordance with Islamic recommendations, sharia banks can increase people's interest in saving using Sharia Bank services by considering research variables, namely increasing knowledge, promotion and location, and further research can add other variables which are also thought to influence interest in saving at Sharia Banks.